2022
DOI: 10.3390/cancers14143432
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Elongation and OPA1 Play Crucial Roles during the Stemness Acquisition Process in Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer with an overall 5-year survival rate of less than 9%. The high aggressiveness of PDAC is linked to the presence of a subpopulation of cancer cells with a greater tumorigenic capacity, generically called cancer stem cells (CSCs). CSCs present a heterogeneous metabolic profile that might be supported by an adaptation of mitochondrial function; however, the role of this organelle in the development and maintenance of CSCs remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Many diseases such as mitochondrial diseases [44,45], metabolic syndrome [46], neurodegenerative diseases [47][48][49][50] and cancer [48,51,52] arise when the mitochondria are perturbed by genetic or environmental toxin-mediated cues causing defects in the structural composition of the mitochondrial membrane, defects in ETC protein complexes, defects of mitochondrial protein import or defects in mitochondrial motility [44,45,49,50,53] among others. However, the impacts of mutations in genes involved in the RAS signalling pathway on mitochondria and energy metabolism have emerged only recently.…”
Section: Energy Metabolism and The Oxidative Phosphorylation (Oxphos)...mentioning
confidence: 99%
“…Many diseases such as mitochondrial diseases [44,45], metabolic syndrome [46], neurodegenerative diseases [47][48][49][50] and cancer [48,51,52] arise when the mitochondria are perturbed by genetic or environmental toxin-mediated cues causing defects in the structural composition of the mitochondrial membrane, defects in ETC protein complexes, defects of mitochondrial protein import or defects in mitochondrial motility [44,45,49,50,53] among others. However, the impacts of mutations in genes involved in the RAS signalling pathway on mitochondria and energy metabolism have emerged only recently.…”
Section: Energy Metabolism and The Oxidative Phosphorylation (Oxphos)...mentioning
confidence: 99%
“…Taking BRCA as an example, previous researchers have demonstrated through in vivo and in vitro experiments that knockdown of OPA1 expression can reduce proliferation migration and invasion of breast cancer cells, and OPA1 silencing can increase miRNA levels of the 148/152 family that inhibit tumor growth and invasion. Therefore, OPA1 has been listed as a drug target for TNBC inhibition [ 28 ]. However, there is no conclusive evidence to explain why upregulation of OPA1 expression is associated with better prognosis in CHOL, CESC, KIRC, READ, and LIHC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers found that upregulation of OPA1 expression was associated with poor prognosis in breast cancer, and the research team reduced proliferation, migration, and invasion of breast cancer cells in vitro and in vivo by inhibiting OPA1 expression. Further research showed that OPA1 silencing inhibited breast cancer cell growth and invasion by up-regulating the expression levels of the 148/152 miRNA family while not reducing mitochondrial respiration [ 28 ]. In pancreatic ductal adenocarcinoma (PDAC), the presence of cancer stem cells (CSCs) was associated with high invasiveness of PDAC, while OPA1 overexpression was found in CSCs and has a regulatory effect on tumorsphere formation [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The population of stem cells in cancer (CSCs) generally show a significant increase in mitochondrial mass, hyperfused mitochondria, and higher mRNA expression of genes involved in mitochondrial biogenesis. Interestingly, the protein Opa1 was found highly expressed in pancreatic ductal adenocarcinoma (PDAC)-derived SCs and positively modulated their propagation in vitro [ 42 ]. A signature of Opa1 upregulation has been reported in triple-negative breast cancer (TNBC), correlating with worse prognosis.…”
Section: Mitochondrial Dynamics Aberrations In Cancermentioning
confidence: 99%